2008
DOI: 10.1021/es8003415
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toluene Degradation Pathways by Two-Dimensional Stable Isotope Fractionation

Abstract: Toluene degradation by several pure and mixed microbial cultures was investigated bytwo-dimensional compound specific isotope analysis (2D-CSIA). For most of the cultures, the respective toluene degradation pathway and toluene attacking enzymatic step was known. The slope of the linear regression for hydrogen (delta delta(2)H) vs. carbon (delta delta(13)C) discrimination (lamda = delta delta(2)H/ delta delta(13)C approximately epsilonH(bulk)/epsilonC(bulk)) was determined in order to characterize aerobic and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
122
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(141 citation statements)
references
References 53 publications
17
122
2
Order By: Relevance
“…3) A phylogeny based on functional genes rather than 16S rRNA gave a better correlation to fractionation factors of dichloromethane-degrading methylotrophic bacteria, as well as toluene-degrading microorganisms (46,47). However, the acetyl-CoA pathway has two distinct initial CO 2 -fixing enzymes (formate dehydrogenase and the carbon monoxide dehydrogenase/acetyl-CoA synthetase complex [48]), which both may contribute to the observed fractionation (Gelwicks et al [2] reported that both branches of the acetyl-CoA pathway show a similar fractionation).…”
Section: Discussionmentioning
confidence: 99%
“…3) A phylogeny based on functional genes rather than 16S rRNA gave a better correlation to fractionation factors of dichloromethane-degrading methylotrophic bacteria, as well as toluene-degrading microorganisms (46,47). However, the acetyl-CoA pathway has two distinct initial CO 2 -fixing enzymes (formate dehydrogenase and the carbon monoxide dehydrogenase/acetyl-CoA synthetase complex [48]), which both may contribute to the observed fractionation (Gelwicks et al [2] reported that both branches of the acetyl-CoA pathway show a similar fractionation).…”
Section: Discussionmentioning
confidence: 99%
“…S1D), the isotope fractionation patterns (characterized by the ⌳ values) are probably influenced by partial reactions preceding the C-H bond cleavage reaction, thus generating various AKIE values. Therefore, we propose that toluene transformation by Bss isoenzymes of obligate and facultative anaerobes may occur via slightly different reaction paths leading to the rate-limiting transition state preceding the C-H cleavage (23). The current mechanistic model for the Bss reaction mechanism predicts that the cleavage of the C-H bond is preceded by the formation of a thiol radical intermediate (see Fig.…”
Section: Fig 1 Plots Of ⌬␦mentioning
confidence: 95%
“…Although toluene in the investigated cultures was always activated by benzylsuccinate synthases, the determined ⌳ values were significantly different, indicating that Bss subtypes in the investigated cultures may show slightly different reaction mechanisms. For facultative anaerobic toluene degraders, the observed ⌳ values were generally smaller than those for obligate anaerobic toluene degraders (23). This result motivated us to investigate the isotope-sensitive steps in the overall reaction in more detail.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Thereby, different pathways of substrate conversion can often be distinguished by the specific isotopic signature of the remaining pool or the product formed Mahieu et al, 2006;Meckenstock et al, 2004;Vogt et al, 2008).…”
mentioning
confidence: 99%